Verbal and Non-Verbal Communication in Product Placement “Descendants of the Sun” - Jonatan Alexander (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study is intended to find out the meaning behind verbal and non-verbal communication in product placement in Korean drama, Descendant of the Sun. Conducting this study, I apply the theory process of signification proposed by Saussure (1974) and Chandler (2007) and Kinesics proposed by Birdwhistell (1970). The subject of this study is verbal and non-verbal communication in product placement in Korean drama Descendants of the Sun. The data was collected through video media from AsianNet.com and several resources. The findings of this study showed that verbal and non-verbal communication in drama DOTS creates the meaningful messages to its viewers. The findings also show that almost everything in the product placement, possibly have communicative purpose to its viewers. This study also found that non-verbal expressions are generally used to support the verbal communication and it is central to interpersonal relations because non-verbal cues are generally important in emotional communication. On the other hand, verbal communication is central to official or formal relationship. Moreover, the verbal and non-verbal communication in product placement mainly have communicative purpose to encourage, inform, persuade even change the opinion to its viewers to buy, use and know more about the products and services.